2023
DOI: 10.21101/cejph.a6325
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among nurses at a military medical academy in Serbia

Abstract: Objectives: Healthcare workers are the professional group at higher risk of burnout than others. It is the underlying reason for medical errors and the general decrease in quality of patient care and is related to poor patient-healthcare worker relationships. Healthcare workers who work with military personnel have specificities compared to healthcare workers who work only with civilians.Methods: A cross-sectional study among 171 nurses at the Military Medical Academy was conducted. The questionnaire consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…In terms of demographic data, our study found no significant associations between gender, marital status, and identity of military with burnout. These findings align with previous studies [ 51 53 ], but contradict research indicating that women are more susceptible to burnout than men [ 54 ]. Furthermore, we observed a significant association between burnout and age among military personnel, consistent with Vojvodic's findings [ 19 , 55 ].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of demographic data, our study found no significant associations between gender, marital status, and identity of military with burnout. These findings align with previous studies [ 51 53 ], but contradict research indicating that women are more susceptible to burnout than men [ 54 ]. Furthermore, we observed a significant association between burnout and age among military personnel, consistent with Vojvodic's findings [ 19 , 55 ].…”
Section: Discussionsupporting
confidence: 88%